Identification of Cancerlectins Using Support Vector Machines With Fusion of G-Gap Dipeptide - Qian, Lili; Wen, Yaping; Han, Guosheng (Frontiers in Genetics, 2020)
The cancerlectin plays an important role in the initiation, survival, growth, metastasis and spread of cancer. Therefore, to study the function of cancerlectin is greatly significant because it help to identify tumor markers and tumor prevention, treatment and prognosis. However, plenty of studies have generated a large amount of protein data. Traditional prediction methods have been unable to meet the needs of analysis. Developing powerful computational models based on these data to discriminate cancerlectins and non-cancerlectins on a large scale has been treated as one of the most important topics. In this study, we developed a feature extraction method to identify cancerlectins based on fusion of g-gap dipeptides. The analysis of variance was used to select the optimal feature set and support vector machine was used to classify the data. The rigorous nested 10-fold cross-validation results demonstrated that our method obtained the prediction accuracy of 83.91% and sensitivity of 83.15%. At the same time, in order to evaluate the performance of the classification model constructed in this work, we constructed a new data set. The prediction accuracy of the new data set reaches 83.3%. Experimental results show that the performance of our method is better than the state-of-the-art methods.